Situation Report: Czechoslovakia, 4 February 1976 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Report on 1975 Plan Fulfillment The Mlada Boleslav Automobile Works: Problems with the GDR? The Atheistic Campaign among Students and the Intelligentsia